Redox properties of a standardized extract of Chenopodium quinoa Willd fruit pericarp modify rat liver GST activities - María Eugenia Letelier; Daniel Rojas-Sepúlveda; Carlos Andrés Gallardo-Garrido (International Journal of Phytomedicine, 2016)
Research of antioxidant properties of herbal thiol compounds is scarce. The main non-enzymatic antioxidant compounds in animal cell are GSH and cysteine. Therefore, in this work, we studied the redox effects of a Chenopodium quinoa Willd (Quinoa) coats extract previously titrated in its polyphenol and thiol compounds. The effects of quinoa extract on rat liver cytosolic and microsomal GSH-transferase was tested. The catalytic active form of this enzyme is its disulphide dimer, and then its reduction provokes its inactivation. Quinoa extract inhibited both enzymatic activities in a concentration-dependent manner. The reducing power of this extract was significantly higher than N-acetyl-cysteine and dithiothreitol. Low concentrations of quinoa extract (without surfactant properties) decrease the apparent Vmax of both cytosolic and microsomal GST, increase their apparent GSH Km and not modify their apparent Km for substrate 1-chloro-2,4-dinitrobenzene. Redox effects of Quinoa extract would be the main cause involved in the inhibition of GSH-transferase activities. Moreover, thiol compounds present in this extract and not polyphenols seem to be the most important reducing agents acting on disulphide bond of GST active dimer. New pharmacological experiments are being carried out in order to evaluate the redox importance of thiol compounds present in this Quinoa extract.